EPDR1, Which Is Negatively Regulated by miR-429, Suppresses Epithelial Ovarian Cancer Progression via PI3K/AKT Signaling Pathway - Zhao, Zhendan; Wang, Zhiling; Wang, Pengling; Liu, Shujie; Li, Yingwei; Yang, Xingsheng (Frontiers in Oncology, 2021)
Epithelial ovarian cancer (EOC) is the main pathological type of ovarian cancer. In this study, we found that ependymin-related 1 (EPDR1) was remarkably downregulated in EOC tissues, and low EPDR1 expression was associated with International Federation of Gynecology and Obstetrics (FIGO) stage, metastasis, and poor prognosis. We confirmed that EPDR1 overexpression dramatically suppressed EOC cell proliferation, migration, and invasion in vitro and in vivo. Mechanistically, EPDR1 inhibited EOC tumorigenesis and progression, at least in part, through the repression of the PI3K (Phosphoinositide 3-kinase)/AKT (AKT Serine/Threonine Kinase 1) signaling pathway. Furthermore, the expression and function of EPDR1 were regulated by miR-429, as demonstrated by luciferase reporter assays and rescue experiments. In conclusion, our study validated that EPDR1, negatively regulated by miR-429, played an important role as a tumor-suppressor gene in EOC development via inhibition of the PI3K/AKT pathway. The miR-429/EPDR1 axis might provide novel therapeutic targets for individualized treatment of EOC patients in the future.